Trace bromide ion impurity leads to formation of chlorobromoaromatic by-products in peroxymonosulfate-based oxidation of chlorophenols. (September 2017) - Fang, Changling; Wang, Zhaohui; Feng, Min; Huang, Ying; Yang, Fei; Liu, Jianshe
Abstract: Trace bromide (Br − ) released from industrial effluents or brominated compounds is able to directly react with peroxymonosulfate (PMS) to generate a series of reactive oxidants which can oxidize and also halogenate organics. We report the identification and evolution of by-products during 2, 4, 6-trichlorophenol (TCP) degradation in the presence of PMS and trace Br − . The influencing factors, including Br − concentration and pH, were investigated. The depletion of TCP was accelerated with increasing trace Br − concentration (0–0.2 mM) and was affected by the initial pH (3.0–7.0). The chlorinated and brominated compounds were identified in simulated wastewater during treatment with PMS. Notably, the potential formation of chlorobromoaromatic by-products was demonstrated for the first time in the presence of PMS and trace Br − . The possible reaction pathways of TCP and its derivatives are discussed. These findings have important implications for the future applications of PMS-based oxidation processes. Graphical abstract: Highlights: Reaction of trace Br − with PMS results in chlorophenol degradation. Chlorobromoaromatic compounds are identified for the first time. The possible reaction pathways of TCP and its derivatives are explained.